Rediseño de un Plan Organizacional para el Mantenimiento de Equipos Mineros. - Recio Cohen, Edinson; Donado Rodríguez, Kevin de Jesús (Universidad Antonio Nariño, 2022)
Maintenance is a fundamental pillar for operations, which plays a very important role important within the processes of any company, its main objective is to have the teams involved directly and indirectly within these available activities, within these controls organizations reliability is paramount within any impact that this may cause the company. Therefore, one of the dilemmas that these have is to find a design organizational standard in their areas for our study in the area of ​​maintenance. In general, the failures that occur in the equipment are for any reason, as long as we attribute it to the planning part or to the technicians, but we do not go further, the lack of organization in these areas is crucial for the times that are required in the availability of the equipment. This lack of organization is reflected in a vicious circle creating aspects negative to the execution of the activities. Companies in their maintenance area and with the aim of being able to redesign organizationally the workplace and be able to carry out the evaluations of the activities developed to teams, look for managerial tools that can efficiently increase maintenance area, maximizing resources and reducing costs, thus improving these maintenance plans.